2015
DOI: 10.1038/srep10590
|View full text |Cite
|
Sign up to set email alerts
|

Paths and determinants for Penicillium janthinellum to resist low and high copper

Abstract: Copper (Cu) tolerance was well understood in fungi yeasts but not in filamentous fungi. Filamentous fungi are eukaryotes but unlike eukaryotic fungi yeasts, which are a collection of various fungi that are maybe classified into different taxa but all characterized by growth as filamentous hyphae cells and with a complex morphology. The current knowledge of Cu resistance of filamentous fungi is still fragmental and therefore needs to be bridged. In this study, we characterized Cu resistance of Penicillium janth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
(113 reference statements)
1
7
0
Order By: Relevance
“…The metal bioaccumulation by GXCR mycelia have well been documented in our previous study40. Taken together with the alive mycelia generated from PVA-SA-conidia beads even after four cycles of successive sorption/desorption of the beads (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…The metal bioaccumulation by GXCR mycelia have well been documented in our previous study40. Taken together with the alive mycelia generated from PVA-SA-conidia beads even after four cycles of successive sorption/desorption of the beads (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Acetyl‐CoA carboxylase, a link between glycolysis and the TCA pathway, is a precursor that initiates fatty acid biosynthesis through acetyl‐CoA carboxylase, which is stimulated by citrate (Akram, ). Glycolysis (Figure a), the TCA (Figure a) and OP (Figure d) were all significantly impaired especially in mutant EC‐6 under high (3 mmol/L) Cu (Figures and ), coinciding with the differential expression of a large number of ATP production‐related genes (Xu et al., ). Additionally, Cu tolerance in both the mutant EC‐6 and WT strain GXCR was significantly increased under exogenous ATP (Figure a and b).…”
Section: Discussionmentioning
confidence: 89%
“…A similar result was obtained in another proteomic study of the yeast strain Rhodotorula mucilaginosa RCL‐11 under Cu stress (Irazusta et al., ). However, a large number of the mRNAs coding various cation transporter proteins was found in the large‐scale transcriptome sequencing of GXCR and EC‐6 under Cu stress (Xu et al., ). Proteins have a longer lifetime than mRNA (Ohno et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MFS, one of the largest families of membrane transporters, are permeases that move a wide variety of organic and inorganic molecules across biological membranes, such as amino acids, sugars, nitrate and phosphate (Yan, 2015). A role for the MFS in fungal metal tolerance was also reported by Majorel et al (2014) who suggest a role for a MFS permease in nickel resistance in the ECM fungus Pisolithus albus, and by Xu et al (2015), who reported for Penicillium janthinellum a crucial role of a MFS in the solute compartmentalization transport related to Cu resistance.…”
Section: O Maius Responses To CD Exposurementioning
confidence: 89%